Impact of a Multicenter, Mentored Quality Collaborative on Hospital‐Associated Venous Thromboembolism. Issue 7 (13th February 2018) - Jenkins, Ian; O'Bryan, Tamra; Holdych, Janet; Maynard, Gregory
Abstract : BACKGROUND: Reliable prophylaxis of hospital‐associated venous thromboembolism (HA‐VTE) is not achieved in many hospitals. Efforts to improve prophylaxis have had uneven results. OBJECTIVE: To reduce HA‐VTE with a scalable quality improvement collaborative. DESIGN: A prospective, unblinded, open‐intervention study with historical controls. PARTICIPANTS AND SETTING: All adult inpatients at 35 community hospitals in California, Arizona, and Nevada. INTERVENTIONS: A centrally supported collaborative implementing standardized VTE risk assessment and prophylaxis. Protocols were developed with 9 "pilot" sites, which received individualized mentoring. Finished protocols were disseminated to 26 "spread" sites, which received improvement webinars without mentoring. Active surveillance for real‐time correction of suboptimal prophylaxis was funded in pilot sites and encouraged in spread sites. Planning and minimal improvement work began in 2011; most implementation occurred in 2012 and 2013. MEASUREMENTS: Rates of per‐protocol prophylaxis (at pilot sites), and compliance with The Joint Commission VTE measures (all sites), were monitored starting in January 2012. The International Classification of Diseases, 9th Edition‐Clinical Modification codes were used to determine the rates of HA‐VTE within 30 days of discharge, heparin‐induced thrombocytopenia, and anticoagulation adverse events; preimplementation (2011) rates were compared with postimplementation (2014) rates. RESULTS: Protocol‐appropriate prophylaxis rates and The Joint Commission measure compliance both reached 97% in 2014, up from 70% to 89% in 2012 and 2013. Five thousand three hundred and seventy HA‐VTEs occurred during 1.16 million admissions. Four hundred twenty‐eight fewer HA‐VTEs occurred in 2014 than in 2011 (relative risk 0.78; 95% confidence interval, 0.73‐0.85). HA‐VTEs fell more in pilot sites than spread sites (26% vs 20%). The rates of adverse events were reduced or unchanged. CONCLUSIONS: Collaborative efforts were associated with improved prophylaxis rates and fewer HA‐VTEs.